2021
DOI: 10.3390/atmos12020155
|View full text |Cite
|
Sign up to set email alerts
|

Dry and Wet Climate Periods over Eastern South America: Identification and Characterization through the SPEI Index

Abstract: A large part of the population and the economic activities of South America are located in eastern regions of the continent, where extreme climate events are a recurrent phenomenon. This study identifies and characterizes the dry and wet climate periods at domain-scale occurring over the eastern South America (ESA) during 1980–2018 through the multi-scalar Standardized Precipitation–Evapotranspiration Index (SPEI). For this study, the spatial extent of ESA was defined according to a Lagrangian approach for moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…These anomalous precipitation and low-level circulation patterns were also similar to the ones registered in the energy crisis in 2001 [91]. In general, the anomalous atmospheric patterns shown in this study were similar to those that occurred in the water crisis in the SEB in 2014 [54], indicating that the dry conditions observed during the 2012-2020 episode over the Upper-SF investigated here have also affected other regions in the country [89,94]. The predominance of the wave pattern with positive pressure anomaly over the SEB may inhibit cloud formation, which can consequently warm the SST, as noted by the positive anomalies of the SST in the South Atlantic (Figure 5a).…”
Section: Middle Sub-middle Lowersupporting
confidence: 85%
See 2 more Smart Citations
“…These anomalous precipitation and low-level circulation patterns were also similar to the ones registered in the energy crisis in 2001 [91]. In general, the anomalous atmospheric patterns shown in this study were similar to those that occurred in the water crisis in the SEB in 2014 [54], indicating that the dry conditions observed during the 2012-2020 episode over the Upper-SF investigated here have also affected other regions in the country [89,94]. The predominance of the wave pattern with positive pressure anomaly over the SEB may inhibit cloud formation, which can consequently warm the SST, as noted by the positive anomalies of the SST in the South Atlantic (Figure 5a).…”
Section: Middle Sub-middle Lowersupporting
confidence: 85%
“…Although not the scope of this study, further investigation of the potential forcing that triggers the wave propagated in the vicinity of Australia is necessary, as well as a more in-depth study on the IASAS and the Southern Atlantic variability. Previous studies showed the importance of the South Atlantic Ocean as a moisture source for Eastern South America [89,[94][95][96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the long-term variability analysis of SAT, we used the CRU time series version 4.03 (resolution = 0.5° × 0.5°) and HadCRUT4 (resolution = 5° × 5°) observational datasets for the period 1901–2018 and 1850–2019, respectively; the HadCRUT4 dataset (available at https://crudata.uea.ac.uk/cru/data/temperature/ ) was primarily used to cover the period not considered by the CRU dataset (1850–1900). The CRU data are derived from the spatial interpolation of monthly climate anomalies of worldwide weather station observations 26 28 and are available at https://crudata.uea.ac.uk/cru/data/hrg/ . These CRU data have been used by many researchers studying long-term temperature and precipitation changes over the EA region 26 , 27 , 29 , 30 and they correlate well with ground station datasets.…”
Section: Methodsmentioning
confidence: 99%
“…We used the CRU time series version 4.03 (resolution = 0.5° × 0.5°) and HadCRUT4 (resolution = 5° × 5°) observational datasets for the period 1901-2018 and 1850-2019, respectively; the HadCRUT4 dataset (available at https://crudata.uea.ac.uk/cru/data/temperature/) was primarily used to cover the period not considered by the CRU dataset . The CRU data are derived from the interpolation of monthly climate anomalies of worldwide weather station observations (Peng et al 2018;Harris et al 2020;Drumond et al 2021) and are available at https://crudata.uea.ac.uk/cru/data/hrg/. These CRU data have been used by many researchers studying long-term temperature and precipitation changes over the EA region (Li et al 2018b;Peng et al 2018;Chen et al 2019;Harris et al 2020) and they correlate well with ground station datasets.…”
Section: Methodsmentioning
confidence: 99%